2000
DOI: 10.1136/ewjm.173.2.94
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to electromagnetic fields and suicide among electric utility workers: a nested case-control study

Abstract: ⅷ Objective To examine mortality from suicide in relation to estimated exposure to extremely low-frequency electromagnetic fields in a cohort of 138,905 male electric utility workers. ⅷ Methods Casecontrol sampling, which included 536 deaths from suicide and 5,348 eligible controls. Exposure was classified based on work in the most common jobs with increased exposure to magnetic fields and indices of cumulative exposure to magnetic fields based on a measurement survey. ⅷ Results Suicide mortality was increased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(5 citation statements)
references
References 47 publications
1
4
0
Order By: Relevance
“…Based on the social withdrawal hypothesis, sedentary behavior increases, resulting in decreased social interactions that in turn result in an increased risk of mental health problems [37]. Occupational analysis of sedentary time and suicidal ideation indicated that craft, equipment, machine-operating, and assembly-line workers had suicidal thoughts more frequently with an increase in sitting time, which was consistent with the findings of another study [38], where workers who engaged in simple, repetitive work were found to be more mentally unstable than active workers, and a significantly higher mortality rate was observed in workers with less exposure to sunlight. Development of workplace interventions is imperative for craft, equipment, machine-operating, and assembly-line workers in accordance with the nature of their job and work environment.…”
Section: Discussionsupporting
confidence: 83%
“…Based on the social withdrawal hypothesis, sedentary behavior increases, resulting in decreased social interactions that in turn result in an increased risk of mental health problems [37]. Occupational analysis of sedentary time and suicidal ideation indicated that craft, equipment, machine-operating, and assembly-line workers had suicidal thoughts more frequently with an increase in sitting time, which was consistent with the findings of another study [38], where workers who engaged in simple, repetitive work were found to be more mentally unstable than active workers, and a significantly higher mortality rate was observed in workers with less exposure to sunlight. Development of workplace interventions is imperative for craft, equipment, machine-operating, and assembly-line workers in accordance with the nature of their job and work environment.…”
Section: Discussionsupporting
confidence: 83%
“…A job‐exposure matrix (JEM)‐based study of 21,744 electrical utility workers in Quebec found no statistically significant association with suicide, 50 nor did an occupational title‐based study of Swedish electricians 51 . Conversely, a nested case‐control study of suicide mortality in a parent cohort of 138,905 male electric utility workers found an association between increasing years of employment as an electrician or line worker and risk of suicide, including a dose–response gradient 52 . This study, however, did not control for important potential confounders such as drug use and mental illness.…”
Section: Epidemiologic Approaches To Determining Work‐relatednessmentioning
confidence: 96%
“…51 Conversely, a nested case-control study of suicide mortality in a parent cohort of 138,905 male electric utility workers found an association between increasing years of employment as an electrician or line worker and risk of suicide, including a dose-response gradient. 52 This study, however, did not control for important potential confounders such as drug use and mental illness. Although the evidence is inconclusive at present, the role of noise and EMF exposures warrant further research.…”
Section: Physical Exposuresmentioning
confidence: 96%
“…Previous suicide attempts, psychiatric disorders, abuse of alcohol and other substances, employment status, financial loss, despair, chronic pain, chronic illness, and family history of suicide have been reported as risk factors for suicide [1]. Environmental factors such as air pollution [2,3], electromagnetic fields [4,5], and season [6][7][8] have also been reported as suicide risk factors.…”
Section: Introductionmentioning
confidence: 99%
“…Epidemiological studies have reported the possibility of an electromagnetic field at electric utility sites or a power line affecting depression and suicide [4,5,9]. In previous research, correlation between geomagnetic disturbances and suicide/depression has been reported in countries such as Canada, South Africa, Finland, Australia, Russia, and Japan [8,[10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%